2015
DOI: 10.14748/sssp.v1i1.1151
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of individuals with disabilities - concepts and concerns

Abstract: INTRODUCTION: The number of people with disabilities has grown tremendously for the last 15 years in Bulgaria. Standardized quality of life instruments can be helpful in the development of public policies which target the needs of this population. The quality of life (QoL) paradigm is a challenging perspective for considering, planning and implementing changes within the area of disabilities. Moreover, an interview with a disabled person about her/his subjective health is a human care with a positive impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
1
4
0
2
Order By: Relevance
“…We establish a predominant influence of the "Environment" and "Physical health" domains while assessing the legal awareness of euthanasia in this vulnerable group in society. The applied multi-regression analysis confirmed the results obtained from the other research methods in the study [5,6]. There is a predominant influence and significant importance of pain and the "Environment" domain on the overall assessment of QL while assessing legal awareness (Table 1): https://doi.org/10.5272/jimab.2022283.4566…”
Section: Resultssupporting
confidence: 73%
“…We establish a predominant influence of the "Environment" and "Physical health" domains while assessing the legal awareness of euthanasia in this vulnerable group in society. The applied multi-regression analysis confirmed the results obtained from the other research methods in the study [5,6]. There is a predominant influence and significant importance of pain and the "Environment" domain on the overall assessment of QL while assessing legal awareness (Table 1): https://doi.org/10.5272/jimab.2022283.4566…”
Section: Resultssupporting
confidence: 73%
“…15 also suggested that education plays a greater role in maintaining health and higher quality of life among mainland Chinese than wealth. However, 35 showed that education did not affect quality of life among disabled individuals.…”
Section: Able-bodied Versus Disabledmentioning
confidence: 95%
“…Also, for individuals who rely on lip reading, understanding healthcare workers wearing medical masks is not possible. Furthermore, we realized that the provision of a patient with disability history or having to sign consent may pose an obstacle, at times not possible for an individual with severe mental or psychosocial disabilities, or on the autistic symptoms [8].…”
Section: Problems With Communication Systemsmentioning
confidence: 99%